PENERAPAN FOOD PHOTOGRAPHY DI RUBRIK KULINER MAKASSARTERKINI.ID (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This research wants to know the process and application of Food Photography. To study this, the researcher has two main problems, namely the Food Photography process in the Makassarterkini.id Culinary Rubric and the application of basic Food Photography techniques in the 22 October 2019 edition of the Culinary Rubric of Makassarterkini.id. The results of this study indicate that there are three focuses in the process of producing food works. photography, including 1) Adjusting the camera lighting, 2) Color composition, 3) Photo editing. Meanwhile, the 22 October 2019 edition of the Makassarterkini.id Culinary Rubric was not analyzed according to the basic techniques of food photography. This is because the composition in the photo is not in accordance with the theory of food photography, namely the application of an object layout where the basil leaves should not be the eye rests so that the fish as the main object is not covered. This problem can affect the meaning of the message the photographer will convey.